PERANCANGAN APLIKASI PENGENALAN KENDARAAN BERMOTOR BERBASIS AUGMENTED REALITY DENGAN METODE MARKERLESS TRACKING - Yengsih, Eeng Nofia; Siyamto, Yuli (Computer Science and Industrial Engineering, 2021)
Augmented Reality is a real illustration depicted through a virtual world explaining the actual situation displayed in the form of video and 3D animation. The advanced features of the smartphone allow using the android operating system. Augmented Reality is relevant as a medium of information, such as information about beat motor spareparts, knowledge about the function of each sparepart and information about the characteristics of damage experienced by motorcycle spareparts. Augmented Reality work system detects objects that have been captured first, this is called a marker. Markerless is an image or involving an object that is detected directly for container that spawns 3D objects in the application. The application design requires Unity software for making AR applications and processing script programs, Vuforia is a database for storing markers. CorelDraw is a graphic design modeling software that is used to make markers. Blender in making 3D objects. Augmented Reality application that is applied to smartphone media using an Android-based operating system. The use of AR applications is expected to be an innovative communication from the workshop to consumers. Consumers also independently analyze and determine what spare parts are being damaged.